2001
DOI: 10.1021/la015611z
|View full text |Cite
|
Sign up to set email alerts
|

Dewetting Induced by Density Fluctuations

Abstract: We consider the stability with respect to dewetting of thin films deposited on a substrate they thermodynamically wet. We show that if density fluctuations with a sufficiently large amplitude appear in a film, the resulting gradient of disjoining pressure in the film destibilizes the free surface eventually leading to the breaking up of the film in droplets. This dewetting mechanism is expected to play a role in films undergoing significant restructuring after deposition or for materials close to a critical po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 31 publications
3
73
0
Order By: Relevance
“…On the other hand, Chung et al [20] have recently shown that the phase separation in thin films of SAN and dPMMA (d ¼ 550 nm) drove the dewetting and the capillary fluctuations failed to explain the dewetting. Liao et al [15] have experimentally demonstrated that the composition fluctuation mechanism [21][22][23][24] induced the dewetting in thermodynamically stable ultrathin blend films of SAN and dPMMA in one phase region. Thus, the dewetting mechanism in blend thin films is still a controversial problem.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Chung et al [20] have recently shown that the phase separation in thin films of SAN and dPMMA (d ¼ 550 nm) drove the dewetting and the capillary fluctuations failed to explain the dewetting. Liao et al [15] have experimentally demonstrated that the composition fluctuation mechanism [21][22][23][24] induced the dewetting in thermodynamically stable ultrathin blend films of SAN and dPMMA in one phase region. Thus, the dewetting mechanism in blend thin films is still a controversial problem.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the correlation of the dewetted holes along the film surface, fast Fourier transition (FFT) was performed by taking There is a peak at q = 0.0044 nm −1 , corresponding to the periodic structures with size of 1400 nm. The result makes it clear that the holes are correlated with each other, which is a typical symbol of spinodal dewetting or dewetting by means of composition fluctuation [27][28][29].…”
Section: Resultsmentioning
confidence: 91%
“…This is the case introduced in [3]. For Γ 0 > 0, the film stability will be enhanced, as discussed in [5,6].…”
mentioning
confidence: 89%
“…The process by which a thin film may become instable and break up into a pattern of holes and droplets, has been attributed to two different mechanisms; nucleation and spinodal dewetting [2]. Recently, Wensink and Jérôme [3] proposed an alternative mechanism that resembles spinodal dewetting. Their idea was that confinement and restructuring of the molecules in the film creates density variations that in turn change the sign of the effective film-substrate interactions, thus leading to the dewetting of a film expected to be stable.…”
mentioning
confidence: 99%